Biomaterials for Testicular Bioengineering: How far have we come and where do we have to go? - Horvath-Pereira, Bianca de Oliveira; Almeida, Gustavo Henrique Doná Rodrigues; Silva Júnior, Leandro Norberto da; do Nascimento, Pedro Gabriel; Horvath Pereira, Bárbara de Oliveira; Fireman, João Victor Barbosa Tenório; Pereira, Maria Laura dos Reis Ferre; Carreira, Ana Claudia Oliveira; Miglino, Maria Angelica (Frontiers in Endocrinology, 2023)
Traditional therapeutic interventions aim to restore male fertile potential or preserve sperm viability in severe cases, such as semen cryopreservation, testicular tissue, germ cell transplantation and testicular graft. However, these techniques demonstrate several methodological, clinical, and biological limitations, that impact in their results. In this scenario, reproductive medicine has sought biotechnological alternatives applied for infertility treatment, or to improve gamete preservation and thus increase reproductive rates in vitro and in vivo. One of the main approaches employed is the biomimetic testicular tissue reconstruction, which uses tissue-engineering principles and methodologies. This strategy pursues to mimic the testicular microenvironment, simulating physiological conditions. Such approach allows male gametes maintenance in culture or produce viable grafts that can be transplanted and restore reproductive functions. In this context, the application of several biomaterial has been proposed to be used in artificial biological systems. From synthetic polymers to decellularized matrixes, each biomaterial has advantages and disadvantages regarding its application in cell culture and tissue reconstruction. Therefore, the present review aims to list the progress that has been made and the continued challenges facing testicular regenerative medicine and the preservation of male reproductive capacity, based on the development of tissue bioengineering approaches for testicular tissue microenvironment reconstruction.